Analysis of Stepper Motor Control Performance in Processing Plastic Waste Into Filament - zulkhairi, Zulkhairi; Syaifudin, Ahmad; Mardhiyyah, Rodhiyah; Kuspranoto, Abdul Haris; alfatih, Muhammad fa’iz (Fidelity : Jurnal Teknik Elektro, 2024)
Based on data from the national waste information system, total waste in Indonesia in 2022 will be 36.1 million tons per year. Referring to this data, there is still a lack of waste processing and requires quite large costs for waste processing resulting from the increase in population, changes in consumption patterns and people's lifestyles. As a solution, researchers have developed a tool to make 3D printing filament using used bottles as the main material. The tool is equipped with a stepper motor that controls the process of winding plastic bottle tape into 3D printing filament. Regulating the rotation of the stepper motor and controlling the tool as a whole uses an Arduino UNO microcontroller and a potentiometer. Based on research results, on PET and PP bottles, speed control results were obtained for PET bottles using a speed of 49 rpm, the results obtained were good with a diameter of 1.75 mm. and for pp bottles it is at a speed of 26 rpm. For the PP type, good quality filament results were obtained with a diameter of 1.75 mm. in further research to use PID control so that PWM changes are more stable for motor rotation, use a power supply with a more stable output, and determine the right angle for cutting plastic bottles to produce the same cut.